2014
DOI: 10.1074/jbc.m114.563593
|View full text |Cite
|
Sign up to set email alerts
|

Extending the Spectrum of α-Dicarbonyl Compounds in Vivo

Abstract: Background: ␣-Dicarbonyls are central intermediates in the formation of advanced glycation end products (AGEs). Results: A quantitation method for the complete spectrum relevant in vivo was established. Conclusion: Non-enzymatic chemistry of glucose and L-ascorbic acid as precursors and ␣-dicarbonyl intermediates play an important role in vivo. Significance: Knowledge of plasma levels of ␣-dicarbonyls is crucial to understand the complex pathways of AGE formation in vivo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
114
2
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 90 publications
(127 citation statements)
references
References 68 publications
3
114
2
2
Order By: Relevance
“…However, derivatization of α-DCs with o-phenylenediamine (OPD) to yield the corresponding quinoxalines has evolved as the most accepted procedure [14]. Furthermore, sample collection and sample preparation were found to have a major impact on the results and have to be strictly controlled [12,[15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…However, derivatization of α-DCs with o-phenylenediamine (OPD) to yield the corresponding quinoxalines has evolved as the most accepted procedure [14]. Furthermore, sample collection and sample preparation were found to have a major impact on the results and have to be strictly controlled [12,[15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…We did not distinguish between the free and reversibly bound ascorbate degradation products in our assay, unlike in a previous study (16). For DHA-Q, two derivatives were detected, as observed by Henning et al (29). Therefore, DHA-Q levels are presented as the sum of those two derivatives.…”
Section: Resultsmentioning
confidence: 81%
“…3-Hydroxykynurenine glucoside (3OHKynG) was synthesized as described previously (28). The quinoxalines of DHA and 2,3-DKG were prepared as described previously (16,29).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This compound was easily synthesized through a one pot procedure, starting from initial oxidation of L-ascorbic acid into dehydroascorbic acid followed by its reaction with o-phenylenediamine. 33,37 Our previous work showed that AAQX selectively interacts with Cu 2+ in methanolic solution, and this reaction was able to be followed through naked-eye and UV-Vis analyses. 33 On the other hand, AAQX is a polyfunctionalized molecule containing alcohol, amine, amide and quinoxaline moieties, which are able to interact with available hydroxyl groups of the cellulose fibers contained in paper via hydrogen bonds, and this fact opened a possibility for immobilizing AAQX on a paper support in attempt to develop a disposable sensor.…”
Section: Synthesis and Copper Ion Screeningmentioning
confidence: 99%